The Effect of Microwave Incinerated Rice Husk Ash on the Compressive and Bond Strength of Fly Ash Based Geopolymer Concrete - Kusbiantoro, Andri; Muhd Fadhil, Nuruddin; Nasir, Shafiq; Sobia, Anwar Qazi (2012)

(untitled)
The development of fly ash and microwave incinerated rice husk ash (MIRHA) blend as the source material for geopolymer concrete was studied through the observation of the hardened specimen strength.Compressive and bonding strength of the specimen indicate the significance of curing temperature in the activation of MIRHA particles. The elevated temperature is presenting a suitable condition for rapid dissolution of silicate monomer and oligomer from MIRHA surfaces, which supports the formation of supersaturated aluminosilicate solution in geopolymer system. It contributes to the refinement of pores structure via the increasing geopolymer gel growth, as observed in the consistent compressive strength development of ambient-cured specimen to the oven-cured specimen. Densification of geopolymer framework appears to be the main contributor to the increasing bonding capacity of geopolymer binder.